The doctor was a woman : stories of the first female physicians on the frontier - Enss, Chris, 1961- (TwoDot, 2024)
"The long-awaited follow up title to Chris Enss's bestselling Doctor Wore Petticoats, profiling 10 new female physicians of the Old West, published in time for Women's History Month. Given the media coverage during the 2020 pandemic, the celebration of the heroics of health care workers and women's work are trending subjects"--